LaUV: A Physics-Based UV Light Simulator for Disinfection and Communication Applications - Maria S. Baltadourou; Konstantinos K. Delibasis; Georgios N. Tsigaridas; Harilaos G. Sandalidis; George K. Karagiannidis (IEEE Access, 2021)
The sterilization properties of the C-band of the ultraviolet (UV) light have been well-known for many years; however, their application has become more vital and widespread today due to the Covid-19 pandemic. Nevertheless, minimal work has been devoted to simulating UV-C propagation for surface disinfection in indoor environments. UV light has also been proposed for non-line-of-sight (NLOS) outdoor communication applications, where a number of simulators have been developed, but with several simplifications. The current work presents a fully-featured simulator for UV light propagation, called LaUV, designed mainly for indoor settings, capable of calculating measurable parameters that can be used for indoor surface disinfection and communication applications. LaUV considers atmospheric absorption and scattering according to Rayleigh and Mie theory, and reflections from rough surfaces. The scattering cross-section and probability density function of the scattering angles (phase function) are calculated accurately for any wavelength, concentration, and diameter distribution of spherical scattering particles (aerosols and droplets). Examples are presented for indoor environments, including empty rooms and rooms with furniture, for different environmental conditions and surface albedos. Interesting initial conclusions can be drawn, considering the spatial distribution of UV exposure for surface disinfection applications and channel modeling for line-of-sight (LOS) and NLOS communication, demonstrating the versatility and the potential applications of the proposed simulator.